Wednesday

April 16, 2014

April 16, 2014

Posted by **Evan** on Tuesday, April 17, 2007 at 6:34pm.

If you have to derive this from first principles, then you have to use the defintion of the Logarithm. E.g. you could use that the Logarithm is the inverse of the exponential function and that the derivative of the exponential function is the exponential function itself.

y = Log(x) -->

x = Exp(y)

dx/dy = Exp(y) = x --->

dy/dx = 1/(dx/dy) = 1/x

**Related Questions**

Calculus - How do you us implicit differentiation to solve x( y + 2 )^5 = 8 x( y...

Property of logarithms - Using property of logarithms, how do I prove derivative...

calculus - find dy/dx y=ln (secx + tanx) Let u= secx + tan x dy/dx= 1/u * du/dx ...

Calculus - Use implicit differentiation to find dy/dx if cos xy = 2x^2 - 3y. I'm...

Calculus (repost) - Use implicit differentiation to find dy/dx if cos xy = 2x^2...

calculus - Use the principles definition to find dy/dx for: y= -3x^2

Calculus - How do you use imlicit differentiation to differentiate e^(xy)? I ...

pre calculous - use the properties of logarithms to write the expression as a ...

Calculus - I am unsure of how to take the derivative of this equation. It may be...

math calculus - Hi could someone please explain to me how i would use the chain ...